ISLAMIC LEADERSHIP, WORK CULTURE, AND EMPLOYEE ENGAGEMENT IN ENHANCING THE INTERNATIONAL REPUTATION OF ISLAMIC HIGHER EDUCATION - Sudirman Sudirman; Sutiah Sutiah; Sarkowi Sarkowi; Yuanda Kusuma; Heida Ifkari Safitri; Ida Fitri Anggarini (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
This study examines the influence of Islamic leadership and work culture on the international reputation of Islamic higher education institutions, with employee engagement as a mediating variable. Using a descriptive quantitative design and PLS-SEM analysis of 555 respondents from five Indonesian state Islamic universities, findings reveal that leadership and work culture indirectly affect international reputation through employee engagement. These results highlight the strategic importance of fostering ethical leadership, a supportive work culture, and engaged employees to strengthen institutional capacity and global recognition. The findings reveal that although Islamic Leadership and Islamic Work Culture do not exert a direct effect on international reputation status, both variables significantly influence it indirectly through Employee Engagement as a mediator. These results contribute to strengthening employee engagement as a strategic component in enhancing organizational capacity within Islamic educational institutions. The strategies derived from this study underscore the importance of leadership roles, Islamic work culture, and employee engagement in improving and sustaining the global reputation of these institutions.